Answer:
The Answer is: The first number is 20 and the second number is -2.
Step-by-step explanation:
Let f = first number and s = second number.
The sum is 18:
f + s = 18
Solve for s:
s = 18 - f
The difference is 22:
f - s = 22
Substitute:
f - (18 - f) = 22
f - 18 + f = 22
2f = 22 + 18
2f = 40
f = 20, the first number.
Solve for s:
s = 18 - f
s = 18 - 20 = -2, the second number.
Proof:
20 + (-2) = 18
20 - 2 = 18
18 = 18
Then:
f - s = 22
20 - (-2) = 22
20 + 2 = 22
22 = 22
Hope this helps! Have an Awesome Day!! :-)